Developing Power Inverter For Motor Drive System In Laboratory - Azidin, Farid Arafat (2005)
In industries power inverters are used in high voltage areas, from JOO Volts to 1000 Volts. Researchers who are concentrating in the design of controlling signal in motor drive system can be in danger when high voltage is involved. lt is not practical to do research in control system using high voltage power inverter when the controlling signal is less than 24 Volts. As an alternative, it is necessary to have a system that can be done safely in a laboratory, which needs low voltage consumption of power inverter. This system can also be applied in the industry. The design of the power inverter in printed circuit board (PCB) is compact and reliable. The complex cooling system for power inverter can be eliminated and it is sufficient by using a heat sink. This power inverter is compatible with the new generation of microcontrollers or digital signal processors (DSP).The heart of this power inverter is a power integrated module from International Rectifier.